Parental Involvement and Students’ Motivation in Learning English - Queen Yumeko Zalvykha Sampelan; Virginia Gabrella Sengkey (Institut Agama Islam Negeri Palopo, 2022)
This study was to determine the level of parental involvement, the level of students' motivation in learning English, and the correlation between parental involvement and students' motivation in learning English. This study used quantitative designs. The instruments of this study were questionnaires adapted from Ekiz and Kulmetov (2015) and Amin, Juriah, and Isa (2001) for measuring parental involvement and an adapted questionnaire for students’ motivation from the Attitude/Motivation Test Battery (2005). This study was conducted to 52 grade 10 – 12 Science students at a private school in Balikpapan enrolled in the first semester of the academic year 2021/2022. The results showed that parental involvement was moderate (M= 3.38). Specifically, parental involvement in terms of parents as motivators was high (M=3.55), while parents as educators (M=3.34) and parents as facilitators (M=3.12) were moderate. Moreover, the results showed that students’ motivation in learning English was high (M=3.82). Specifically, intrinsic motivation was high (M=4.17) and extrinsic motivation was moderate (M=3.40). Lastly, it was found that there was a significant correlation between parental involvement and students’ motivation in learning English as the results show p=.000 < 0.005, r=.537. Therefore, it is recommended that parents be more involved so students can be more motivated in learning English.